Deep Learning and Its Application in the Field of Rail Transit - XIONG Qunfang; LIN Jun; LIU Yue; YUAN Hao; YOU Jun (Kongzhi Yu Xinxi Jishu)
Deep learning has shown great potential and advantage in feature extraction and image recognition. In recent years, more and more researches have focused on the application of deep learning in rail transit. It introduced the current state of deep learning and its application in the field of rail transit, including identification, driver fatigue detection, lane detection and vehicle recognition equipment fault detection. Additionally, it summarized the main functions and existing problems of deep learning in the field of rail transit, and presented some prospects of future work.